Overview on current criteria for heavy metals and its hint for the revision of soil environmental quality standards in China - Shi-bao CHEN; Meng WANG; Shan-shan LI; Zhong-qiu ZHAO; Wen-di E (Journal of Integrative Agriculture, 2018)
Following rapid social and economic development over the past several decades, soil pollution by heavy metals (HMs) has been both serious and widespread in China. The Soil Environmental Quality Standards (SEQSs) in China (GB 15618-1995) have been introduced to encourage and enforce sustainable soil HM management. However, in recent years, HM contents in soils have frequently been found to exceed their associated standard values, while the crops growing on them might still meet regulatory standards, and vice versa. There is thus growing awareness that GB 15618-1995 does not effectively regulate current soil HM pollution, as it has encountered bottlenecks, and disappointing outcomes caused by poor execution along with deficiencies and gaps in the policies. However, due to the deficiency of scientific research about relationships between soil HM concentrations and their ecological or human health effects, the development of SEQSs in China is still greatly restricted. This paper discusses international SEQSs of HMs as well their development in China over time, then examines current Chinese SEQSs to demonstrate their potential regulatory deficiencies by referring to international SEQSs. The corresponding legislative policies are described, and scientific information or responses are outlined for maintaining soil environmental quality. China's experience has shown that policy and science can be linked to work in tandem to better understand and manage soil quality issues.